2016
DOI: 10.1097/bot.0000000000000475
|View full text |Cite
|
Sign up to set email alerts
|

Character, Incidence, and Predictors of Knee Pain and Activity After Infrapatellar Intramedullary Nailing of an Isolated Tibia Fracture

Abstract: Objective To study the activity and incidence of knee pain after sustaining a isolated tibia fracture treated with an infrapatellar intramedullary nail at one year. Design Retrospective review of prospective cohort Setting Multicenter Academic and Community hospitals Patients 437 patients with an isolated tibia fracture completed a 12 month assessment on pain and self-reported activity. Intervention Infrapatellar Intramedullary Nail Outcomes Demographic information co-morbid conditions, injury charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
8
1
2
Order By: Relevance
“…16 Obremskey et al, found out that in their study smoking, comminuted fractures, and surgeons with less than 5 years of experience were some predictors of knee pain. 17,18 Darabos et al studied patients, who had undergone intramedullary nails and evaluated the distance from the tip of the nail to the tibial plateau and tibia tuberosity on lateral knee radiographs. It was concluded that the position of the tip of the nail and its adverse impact on the innervation pattern of the area dorsal to the patellar tendon could lead to anterior knee pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Obremskey et al, found out that in their study smoking, comminuted fractures, and surgeons with less than 5 years of experience were some predictors of knee pain. 17,18 Darabos et al studied patients, who had undergone intramedullary nails and evaluated the distance from the tip of the nail to the tibial plateau and tibia tuberosity on lateral knee radiographs. It was concluded that the position of the tip of the nail and its adverse impact on the innervation pattern of the area dorsal to the patellar tendon could lead to anterior knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the studies, 11% of the patients treated with intramedullary interlocking nails had clinically significant anterior knee pain after 1 year of follow-up. 5 Causes of anterior knee pain following intramedullary interlocking nail include skin incision, injury to the intra-articular structures, size of tibial plateau and damage to the infrapatellar branch of the saphenous nerve. 6 Several studies in the literature have shown that the position of the proximal nail tip may be one of the causative factors of anterior knee pain after tibia nailing.…”
Section: Introductionmentioning
confidence: 99%
“…Большое внимание авторы уделяют выбору доступа к точке введения стержня через связку надколенника или рядом с ней [20,22,28,29,30]. S.K.…”
Section: Discussionunclassified
“…Лечение боли в коленном суставе после интрамедуллярного остеосинтеза представляется трудной задачей. Большинство авторов сообщают, что удаление стержня не приводит к купированию болевого синдрома, а в ряде случаев даже ведет к его усилению [9,19,28]. Удаление стержня эффективно в тех случаях, когда он упирается в надколенник или в его связку [28].…”
Section: Discussionunclassified
“…[ 8 11 ] However, IMN fixation is not without its own unique complication profile including higher rates of anterior knee pain ranging from 11% to 23% based on recent prospective studies and metanalyses. [ 12 17 ]…”
Section: Introductionmentioning
confidence: 99%